2002
DOI: 10.1007/bf02345074
|View full text |Cite
|
Sign up to set email alerts
|

Development andin vitro validation of a device for measuring non-shunt cardiac output by nitrous oxide throughflow

Abstract: A system has been developed for measuring non-shunt cardiac output by the throughflow technique, using nitrous oxide in patients undergoing general anaesthesia. The throughflow measurement technique is a non-invasive method based on inert gas throughflow theory. In vitro validation of the measurement system was performed using a lung gas exchange simulator. The accuracy and precision of the throughflow measurement system was assessed by comparing measured and target values for five simulated values of non-shun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The acceptable lower limit for marker N 2 concen-tration depends on the standard deviation of the measurement of N 2 concentration in fresh and exhaust gas streams. We have found that, in our system, which used fully mixed gas streams without tidal variations in gas concentrations, acceptable scatter in measured uptake for all gases for clinical purposes is achieved with fresh gas N 2 concentration of ϳ30% (6,17,21).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The acceptable lower limit for marker N 2 concen-tration depends on the standard deviation of the measurement of N 2 concentration in fresh and exhaust gas streams. We have found that, in our system, which used fully mixed gas streams without tidal variations in gas concentrations, acceptable scatter in measured uptake for all gases for clinical purposes is achieved with fresh gas N 2 concentration of ϳ30% (6,17,21).…”
Section: Discussionmentioning
confidence: 98%
“…This was chosen as it lay midway within the measurement range of the multigas analyzers for CO 2. For both the extractable marker method and the Haldane method, marker gas flows (CO 2 and N2) were monitored continuously from gas supply pressures (measured with solid-state pressure transducers) at a high-pressure gas source (cylinders of compressed medical air and CO 2 in conjunction with variable pressure regulators, delivering pressures of 400 -460 kPa) and the previously determined pressure-flow characteristics of a series of hollow-wire gas flow resistors (see APPENDIX) (6,21). It was found during bench testing that, at this flow rate, full extraction of CO 2 was ensured for 3-4 h before depletion of the soda lime on the fresh gas side became significant, using two standard 1-liter cannisters in series containing soda lime (Medisorb).…”
Section: System Design the Mathematical Basis Is Outlined In The Appmentioning
confidence: 99%
See 1 more Smart Citation
“…17 At these points, thorough mixing will ensure stable gas concentrations in the face of tidal fluctuations in concentration at the mouthpiece, which improves accuracy and precision of the measurement. Indirect calorimetric methods such as this can be automated to provide ongoing measurement, 18 but need repeated switching of gas sampling to achieve this, which limits the frequency of measurement and precludes truly continuous gas exchange monitoring. The continuous method tested here is an adaptation of the Haldane transformation and requires the presence of some N 2 in the exhaust gas flow in order to compute Equation (1).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid reliance on visual reading of rotameters which may be imprecise, flows into the system were continuously measured by a previously described technique [4]. This uses continuous monitoring of air supply pressure from a high‐pressure source (medical air cylinders) using a pressure transducer and the previously calibrated pressure‐flow characteristics of one or more gas flow resistors.…”
Section: Methodsmentioning
confidence: 99%